Textile Industrial Effluents: Implication and Possible Use for Afforestation in Western Rajasthan - Aggarwal, R K; Kumar, Praveen (Annals of Arid Zone, 2016)
In this paper, the environmental problems related to industrial effluentswith particular reference to western Rajasthan are discussed. In Jodhpurdistrict alone, textile effluents constituting major source are dischargeduntreated at the rate of 7 million litres/day. The effluents are colouredwith high pH (9-11), predominant in sodium (600-3500 ppm) having high RSCvalues (11-90 me/I), very low in calcium, magnesum, lead and cadmium.Effluent can possibly be used for establishing tree species of economic valueand the soil deterioration can be reduced by giving Some soil treatments.